MEDB-50. Assessment of cellular radiosensitivity and DNA repair in medulloblastoma cell lines and patient-derivded xenograft slice cultures. (3rd June 2022) - Feyerabend, Simon; Rieckmann, Thorsten; Riepen, Britta; Oetting, Agnes; Christiansen, Sabrina; Schoof, Melanie; Hardt, Annika; Köcher, Sabrina; Neumann, Julia; Schwarz, Rudolf; Mack, Norman; Schwalm, Benjamin; et al.
Abstract: Medulloblastoma (WHO grade 4) is the most common malignant brain tumor of childhood. Despite the high importance of radiotherapy for disease control, the mechanisms underlying response and resistance to radiotherapy are incompletely understood. Therefore, we assessed the radiosensitivity and DNA repair capacity of medulloblastoma cell lines in-vitro and of patient-derived xenograft (PDX) models ex-vivo. Cell survival after irradiation of seven medulloblastoma cell lines displaying different subgroups was assessed via colony formation assay (DAOY, UW228, UW473, SJMM4, ONS-76, HDMB-03, D283). The ONS-76 and the mouse SJMM4 cell line were the most radioresistant strains (surviving fraction after 6 Gy (SF6): 0.33 and 0.31, respectively), followed by UW473, UW 228 and DAOY cells (SF6 0.16-0.21). The non-WNT/non-SHH-activated cell lines HDMB-03 and D283 cells demonstrated profoundly higher cellular radiosensitivity (SF6 <0.05). Analysis of residual (24h after irradiation) DNA double-strand breaks (DSB) as assessed by co-localized γH2AX/53BP1-foci demonstrated a significant correlation between DSB repair capacity and cellular survival. To use a more reliable pre-clinical model for medulloblastoma, we further examined DNA repair foci in ex-vivo irradiated slice cultures of PDX models MED-113 (SHH) and NCH2194 & HT028 (Gr. 3). Immunofluorescence analyses of frozen sections demonstrated non-hypoxic (pimonidazole-negative) and proliferating (EdU-positive) cells at the outer rim of the tumor slices. Two hours after irradiation all three PDX models showed a strong increase in 53BP1-foci, clearly indicating DNA damage induction. Most radiation-induced DSB were repaired after 24h. In a first radiosensitization approach, we treated the HT028 model with the PARP inhibitor olaparib (1µM ± 2Gy irradiation). Twenty-four hours after treatment the sample displayed a strong increase in the amount and size of 53BP1-foci, indicating compromised DNA repair. Further in-vitro and ex-vivo investigations with the aim to predict individual radiosensitivity and effective radiosensitization strategies are ongoing.